La régulation par un organisme administratif autonome comme modèle de contrôle et de participation - Issalys, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
In this paper, the control and participative functions of the public administration are viewed as a two-way stream of information. More specifically, this model is applied to regulatory agencies in Canada and Québec. The downward, control-oriented flow and the upward, participative flow of information are both traced by means of an analysis of the key elements in the legal and administrative structure of regulatory agencies. Specific illustrations are drawn mainly from the field of energy regulation in Canada and Québec. Examination of the model in this context suggests that efficiency in the control and participative functions of regulatory agencies can be achieved only through the preservation of a proper balance among the various features of a regulatory scheme, both within and around the agencies.